(3GdCQHYhfs - (3GdEQHdj, SYO Hf EHQGgje Hf GdMSf Hf Ydj,s
(3ChdgG (B:s
...(3cfJ SeYJ Ydi cKjQ ef eTGjN GdMOjK Cf GdfHj (B-(3Udi Gddg Ydjg hSde(B- (3bGd (B" (3ef MaX Ydi CeJj CQHYjf MOjKG cfJ TajYG dg jhe GdbjGeI(B" ...s
(3BNQgG (B:s
(3eHJhQI GdBNQ, hBNQ GdehLhO efgG bhdg(B: ... (3abGd YHO Gddg(B: (3eG Cbhd aj WjfI YLfJ HeGA GdQSGdI hTLQI ZQSJ HeGA GdhMj(B...s
(3fSNI ebGHdIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI(B:(3L(B1(3,U(B414(3,Qbe(B2155s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdMOjK hGdeUWdMs